Petrogenesis and geological implications of the qiyishan triassic granitoids in east Beishan orogen, inner Mongolia, NW China: evidence from geochronology, geochemistry and Nd-Hf isotopes - Liu, Ruiqin; Chen, Chao; Lv, Xinbiao; Zhang, Zhongcheng; Ruan, Banxiao; Zhang, Shanming; Hu, Erhong (Frontiers in Earth Science, 2023)
The Qiyishan deposit is a large-scale Rb polymetallic deposit in the Beishan orogen. However, there remain debates regarding its metallogenic age and tectonic setting. In addition, studies of Triassic tectono-magmatic events in the Beishan orogen are still insufficient, and conducting genesis studies on the Qiyishan Triassic granitoids will help to enhance the understanding of Triassic magmatism and tectonic evolution in the Beishan orogen. In this contribution, we report new data for the ore-forming granitoids of Qiyishan deposit, including zircon U-Pb ages, major and trace element concentrations and Nd-Hf isotope compositions to define the ages and genesis of the Qiyishan granitoids and discuss their origin and geodynamic implications. Zircon U-Pb dating of the Qiyishan ore-forming granitoids yielded three ages of 217.5±1.3 Ma, 217.2 ±0.8 Ma, and 207.5±2.0 Ma, respectively. The age of Rb mineralization can be constrained to 207.5± 2.0 Ma, while the age of W-Sn-Mo mineralization is considered to be younger than approximately 217 Ma. The Characteristics of major and trace elements of the rock samples indicate that the Qiyishan granites can be classified to highly fractionated I-type granite, and characterised by a transition to A-type like granite to some extent. The granites were not only affected by fractional crystallisation, but underwent magmatic-hydrothermal interaction. The zircon εHf(t) values of the Qiyishan granitoids ranged from 3.28 to 16.07 and the Hf model age (TDMc) ranged from 0.216 to 1.042 Ga, revealing that the Qiyishan granitoids originated from the partial melting of both mantle and crustal sources. εNd(t) values ranged from -0.52 to -0.25, with Nd model ages of 0.998Ga to 1.007 Ga. These results indicate that the granitoids originated from the mantle-derived magmas intruding into the lower crust within an intracontinental extensional environment. Combining the previous studies of Triassic granites in the Beishan orogen and this work, the Triassic granites exhibit a transition from I-type to A-type along the northeast direction, indicating a decrease in the contribution of ancient crustal to the magma source. We propose that the Qiyishan granitoids formed in a transitional tectonic environment, signifying the shift from post-orogenic to intracontinental extensional settings in beishan orogen during late Triassic.